Assessment of genetic variability in Hill cattle of Garhwal region of Uttarakhand by microsatellite markers - PRAKASH, B; PUNDIR, R K; SINGH, P K (The Indian Journal of Animal Sciences, 2012)
Knowledge of livestock genetic diversity is a crucial step to respond to commercial requirements and achieve production objectives in different environments and production systems. We investigated population genetic diversity in a hitherto unexplored Hill cattle population of Garhwal region of Uttarakhand state using microsatellite markers. A total of 48 individuals belonging to the Garhwal Hill cattle population were typed with 21 microsatellites. A mean of 12.61±4.80 alleles per locus was typed, indicating high allelic diversity in the population. The mean number of effective alleles per locus was 5.66±2.64. The studied population had high gene diversity indicated by high mean observed and expected heterozygosities across the 21 loci, i.e. 0.699±0.19 and 0.721±0.10 respectively. Mean PIC across the investigated loci was 0.782±0.10. The mean F1’s value was 0.118±0.17 indicating inbreeding in the population. Genetic bottleneck evaluated by IAM, TPM and SMM methods as well as frequency distribution was found to be absent in the evaluated population.